Stroke Ready Intervention: Community Engagement to Decrease Prehospital Delay. Issue 5 (20th May 2016) - Skolarus, Lesli E.; Zimmerman, Marc A.; Bailey, Sarah; Dome, Mackenzie; Murphy, Jillian B.; Kobrossi, Christina; Dombrowski, Stephan U.; Burke, James F.; Morgenstern, Lewis B.
Abstract : Background: Time‐limited acute stroke treatments are underused, primarily due to prehospital delay. One approach to decreasing prehospital delay is to increase stroke preparedness, the ability to recognize stroke, and the intention to immediately call emergency medical services, through community engagement with high‐risk communities. Methods and Results: Our community–academic partnership developed and tested "Stroke Ready, " a peer‐led, workshop‐based, health behavior intervention to increase stroke preparedness among African American youth and adults in Flint, Michigan. Outcomes were measured with a series of 9 stroke and nonstroke 1‐minute video vignettes; after each video, participants selected their intended response (primary outcome) and symptom recognition (secondary outcome), receiving 1 point for each appropriate stroke response and recognition. We assessed differences between baseline and posttest appropriate stroke response, which was defined as intent to call 911 for stroke vignettes and not calling 911 for nonstroke, nonemergent vignettes and recognition of stroke. Outcomes assessments were performed before workshop 1 (baseline), at the conclusion of workshop 2 (immediate post‐test), and 1 month later (delayed post‐test). A total of 101 participants completed the baseline assessment (73 adults and 28 youths), 64 completed the immediate post‐test, and 68 the delayed post‐test. All participants were African American. The median age of adults was 56 (interquartile range 35–65) and of youth was 14 (interquartile range 11–16), 65% of adults were women, and 50% of youths were women. Compared to baseline, appropriate stroke response was improved in the immediate post‐test (4.4 versus 5.2, P <0.01) and was sustained in the delayed post‐test (4.4 versus 5.2, P <0.01). Stroke recognition did not change in the immediate post‐test (5.9 versus 6.0, P =0.34), but increased in the delayed post‐test (5.9 versus 6.2, P =0.04). Conclusions: Stroke Ready increased stroke preparedness, a necessary step toward increasing acute stroke treatment rates. Clinical Trial Registration: URL:https://www.clinicaltrials.gov/ . Unique identifier: NCT01499173.